2017
DOI: 10.18632/oncotarget.20776
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic role of neutrophil lymphocyte ratio in patients with spontaneous intracerebral hemorrhage

Abstract: The aim of this study was to evaluate the prognostic role of neutrophil lymphocyte ratio (NLR) in patients with spontaneous intracerebral hemorrhage (ICH). PubMed, EMBASE, Web of Knowledge, Cochrane Library and China National Knowledge Infrastructure were searched for potentially relevant literature. The study and patient characteristics were extracted. Odds ratios (ORs) with 95% confidence intervals (CIs) were pooled to estimate the prognostic role of NLR in patients with ICH. Poor functional outcome was defi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
15
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 33 publications
(55 reference statements)
1
15
0
1
Order By: Relevance
“…At the same time, in accordance with the results of our multivariate logistic regression analysis, ANLR significance as an independent predictor was demonstrated to only verify the functional prognosis of SSICH acute period outcome. The obtained data accord with the results of a meta-ana lysis conducted by J. Zhang [et al] (2017), which revealed that higher NLR was associated with a poorer functional outcome at 3 months, while higher NLR was not associated with higher risk of death at 3 months [19]. A study by A. Giede-Jeppe et al (2017) also revealed that patients with an ANLR under the 25 th percentile -compared to patients with an ANLR above the 25 th percentile presented with a better clinical status, lower hematoma volumes on admission and showed a better functional outcome [5].…”
Section: Discussionsupporting
confidence: 90%
“…At the same time, in accordance with the results of our multivariate logistic regression analysis, ANLR significance as an independent predictor was demonstrated to only verify the functional prognosis of SSICH acute period outcome. The obtained data accord with the results of a meta-ana lysis conducted by J. Zhang [et al] (2017), which revealed that higher NLR was associated with a poorer functional outcome at 3 months, while higher NLR was not associated with higher risk of death at 3 months [19]. A study by A. Giede-Jeppe et al (2017) also revealed that patients with an ANLR under the 25 th percentile -compared to patients with an ANLR above the 25 th percentile presented with a better clinical status, lower hematoma volumes on admission and showed a better functional outcome [5].…”
Section: Discussionsupporting
confidence: 90%
“…A meta-analysis by Zhang [18] evaluating the prognostic value of NLR in patients with ICH revealed that higher NLR was associated with higher risk of poor neurological functional outcome, but not higher mortality at 90-day. Another meta-analysis by Zengpanpan [19] showed that higher NLR predicted higher risk of 90-day mortality and in-hospital mortality, but not poor neurological functional outcome.…”
Section: Discussionmentioning
confidence: 99%
“…[24,29] Acute brain injury also causes the inactivation of lymphocytes, which greatly weaken host immune system. [18] Eventually, it may result in infectious complications, which are the main cause of poor prognosis in ICH patients. [18] Therefore, higher NLR represents elevated neutrophils (intense inflammatory response) or decreased lymphocytes (impairment of host defense), which would lead to a poor outcome in ICH.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Its superior predictive value for clinical outcomes has been demonstrated in patients with major cardiac events, ischemic stroke, diabetes mellitus, chronic obstructive pulmonary disease, cancers, sepsis, infectious pathologies, and liver failure [1318]; however, the association between NLR and clinical outcomes of sICH remains controversial. Previous studies premise that high NLR reflects an elevation of neutrophils and down-regulation of lymphocytes in peripheral blood, is an independent predictor of poor clinical short-term outcomes after sICH [1922]. However, other studies have demonstrated that NLR has no significant effect on mortality, and 30- or 90-day poor outcomes [23, 24].…”
Section: Introductionmentioning
confidence: 99%